Minimum Delay Node Scheduling Algorithm for Wireless Sensor Network - Taoshen Li; Jun Tang; Junbin Liang; Hongxing Lan (Dianxin kexue)
In wireless sensor networks,saving energy and reducing delay are always the focus of research and difficult problems. In order to solve that problem, a new minimum delay scheduling（MDS）algorithm was proposed. Through the analysis and calculation of energy and delay of nodes, this algorithm may calculate the node energy threshold. To realize minimum network delay and it always selects the node whose remaining energy was in the limited range and had the minimum delay to be next top node.Theoretical analysis and simulation results show that MDS algorithm can control the lifetime of network within an acceptable range while effectively minimizing network delay comparing with previous algorithms.